1993
DOI: 10.1093/nar/21.12.2907
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP response element binding protein, CREB, is a potent inhibitor of diverse transcriptional activators

Abstract: Cyclic AMP response element binding protein (CREB) activates transcription of cAMP response element (CRE)-containing promoters following an elevation of intracellular cAMP. Here we show that CREB and the highly related protein ATF-1 are also potent transcription inhibitors. Strikingly, CREB inhibits transcription of multiple activators, whose DNA-binding domains and activation regions are unrelated to one another. Inhibition requires that the CREB dimerization and DNA-binding domains are intact. However, inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Although CREB is mostly described as a positive transcription factor, several reports have shown that it can also inhibit the transcription activity of diverse promoters such as those of c-fos, 38 5-amino-leavulinate synthase, 39 and somatostatin 40 genes. Lemaigre et al 41 showed that CREB, after dimerization, inhibits diverse transcriptional activators. Previous studies have also shown that Ang II inhibits adenylyl cyclase activity and intracellular accumulation of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Although CREB is mostly described as a positive transcription factor, several reports have shown that it can also inhibit the transcription activity of diverse promoters such as those of c-fos, 38 5-amino-leavulinate synthase, 39 and somatostatin 40 genes. Lemaigre et al 41 showed that CREB, after dimerization, inhibits diverse transcriptional activators. Previous studies have also shown that Ang II inhibits adenylyl cyclase activity and intracellular accumulation of cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, CREB is activated via phosphorylation induced by several distinct signals (protein kinase A [PKA], Ca2+, and transforming growth factor 1) (12,22,30,48) and through interactions with cell-specific transcription factors (4,40). In addition to acting as an inducible activator, CREB can function as a constitutive activator (36) or as a potent inhibitor of a diverse class of transcriptional activators (35). The molecular mechanisms that allow CREB to act in such a malleable manner are poorly understood.…”
mentioning
confidence: 99%
“…Interestingly, both the wt and a dominant-negative CREB mutant inhibited the IL-2 promoter activity, suggesting that CREB may be acting and inhibiting as a part of a protein complex, rather than directly binding to the target sequence. It was indeed reported previously that CREB can serve as a repressor of various promoters and this function is not associated with CRE element binding or activator binding (20). One possibility is that binding of CREB or CREB-containing complexes prevents binding or assembly of other activating complexes, which exhibit higher affinity for the SM-derived sequence; however, the inhibitory effect of CREB per se is independent of the differences in sequence between the species.…”
Section: Discussionmentioning
confidence: 92%
“…The construct pIL2PSMDBL was obtained similarly by first generating 5Ј and 3Ј parts of the SM-proximal promoter using primers 5Ј-CTGACAGAATGGATGACCCCCAAAGACTGACA-3Ј and 5Ј-CATCCATTCTGTCAGTCTTTGGGGGT-3Ј together with IL2PU or IL2PD and subsequent PCR splicing, as above, leading to a duplication of the Ϫ180 site from SM. The plasmids expressing CREB and dominantnegative A-CREB were gifts from M. Green (University of Massachusetts, Worcester, MA) and C. Vinson (National Cancer Institute, Bethesda, MD) (20,21). Plasmids expressing p300 were a gift from K. Gardner (22).…”
Section: Il-2 Promoter Constructs and Transfectionsmentioning
confidence: 99%